ANALISIS PENYELENGGARAAN DAN PENYIAPAN BAHAN PENYUSUNAN ANGGARAN DPRD PROVINSI LAMPUNG BERDASARKAN PASAL 10 AYAT (2) HURUF A PERATURAN GUBERNUR NOMOR 60 TAHUN 2016 (Studi Pada Bagian Sekretariat DPRD Provinsi Lampung) - Purwanto Joko; Ansori Ansori (Universitas Bandar Lampung (UBL), 2022)
The Regional People's Representative Council (DPRD) as an institution and a reflection of a democratic government, so that in carrying out the administration of regional government it does not deviate from existing norms and statutory regulations and other guidelines that have been jointly determined. In the context of the budget of a public sector organization, the budget includes plans for how much the plan will cost and how much and how to get the money to fund the plan. In the Governor's Regulation Number 60 of 2016 Article 10 the Finance Section has the task of preparing budget preparation materials, budget amendments, carrying out financial management and preparing financial accountability reports for the DPRD Secretariat and Provincial DPRD. The problem of this research is how to analyze the implementation and preparation of materials for the preparation of the Lampung Provincial DPRD budget based on Article 10 Paragraph (2) Letter A Governor Regulation Number 60 of 2016. The research method uses a normative juridical approach and an empirical approach using secondary data and primary data, then carried out qualitative juridical data analysis. Research results, analysis of the implementation and preparation of budget preparation materials for the DPRD of Lampung Province Based on Article 10 Paragraph (2) Letter A Governor Regulation Number 60 of 2016, it is necessary to have budget transparency in accordance with the activities carried out by the Secretariat Section in the Lampung Provincial People's Legislative Council, so that in its implementation in accordance with the expenditure of activities in the Secretariat of the Regional House of Representatives of Lampung Province, and the need to improve quality when managing the budget, so that with the improvement in performance it is expected that the efficiency of budget use will increase so that the budget is carried out optimally.